2023
DOI: 10.3389/fspor.2023.1128075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an 8-week multimodal program on thoracic posture, glenohumeral range of motion and serve performance in competitive young tennis players

Abstract: IntroductionIntensive tennis practice is known to generate sport-specific adaptations at the shoulder region and influence the sagittal spinal curvature. However, increased thoracic kyphosis decreases the shoulder functional capacity, which could limit tennis performance. Therefore, the aim of this study was to investigate the effects of an 8-week multimodal program on thoracic posture, glenohumeral range of motion, and serve performance in competitive young tennis players.MethodsEighteen male and four female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…1 ). 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 16 , 17 , 18 , 19 , 21 , 22 , 25 , 27 , 28 , 29 , 30 , 33 , 34 , 35 , 36 Of the 25 studies, 5 only reported the ROM for the dominant shoulders, while 20 studies reported the ROM for both dominant and nondominant shoulders ( Table II ). Of the 25 studies, 12 measured the ROM with a goniometer, 10 with an inclinometer, 1 using photographs, 1 using a motion analysis system, and 1 using a dynamometer ( Table I ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 16 , 17 , 18 , 19 , 21 , 22 , 25 , 27 , 28 , 29 , 30 , 33 , 34 , 35 , 36 Of the 25 studies, 5 only reported the ROM for the dominant shoulders, while 20 studies reported the ROM for both dominant and nondominant shoulders ( Table II ). Of the 25 studies, 12 measured the ROM with a goniometer, 10 with an inclinometer, 1 using photographs, 1 using a motion analysis system, and 1 using a dynamometer ( Table I ).…”
Section: Resultsmentioning
confidence: 99%
“…As this test is widely used by coaches and several federations to classify the level of their players based on a number of technical and physical characteristics, it was expected that there would be some evidence on this topic. On the contrary, it was only found that studies with a pre- vs. posttest mainly used the ITN to classify their sample, but not to understand the underlying effects of the ITN ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%